Analysis of Learning Community at SD Negeri 236 Palembang - Heriyani, Heriyani; Kristiawan, Muhammad; Mulyadi, Mulyadi (PPSDP International Journal of Education, 2025)
This study aims to analyze teacher learning communities in improving teacher performance in elementary schools. Using a narrative qualitative method, this study involved 20 elementary school teachers in Plaju District, Palembang City. Data were collected through in-depth interviews, participant observation, and document analysis. The results of the study indicate that teacher learning communities play a significant role in improving teacher performance through collaboration, critical reflection, and evidence-based practices. Participation in learning communities improves teachers’ abilities in planning, implementing, and evaluating learning. This study highlights the importance of policy support to develop and expand teacher learning community programs as an effective strategy in teacher professional development.